Pengembangan Development of STEM-Based Physics Learning Modules and Their Impact on Students' Scientific Literacy Skills - Muftihatur Rahma; Helmi; Kaharuddin Arafah (Jurnal Penelitian Pendidikan IPA, 2025)
This research is a Research and Development (R&D) study that uses the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation.  The purpose of this study is to develop a STEM-based physics learning module and test its validity, practicality and effectiveness in improving students' scientific literacy skills. Validation was conducted by three experts who assessed the module and the science literacy test. Ten physics teachers assessed the module's practicality. The effectiveness test was conducted using a quasi-experimental design with a posttest only control group design model in two classes, namely the experimental class (32 students) and the control class (31 students), both from SMAN 13 Takalar. The instruments used in this study were the validation sheet of the STEM-based physics learning module, the practicality sheet, and the validated students' scientific literacy ability test. The research findings revealed that the module was valid and suitable for use with a validity score of 0.80; teacher responses indicated that the module was very practical with an average score of 93.8%; and the t-test results showed that the average posttest score of the experimental class students was significantly higher than the control class, with a t-count value = 4.54 greater than t-table = 1.77 at a significance level of 5%. Based on these results, the STEM-based physics learning module is considered valid, highly practical, and effective in improving students' scientific literacy skills.